2018
DOI: 10.1038/aps.2017.134
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinol alleviates impaired bone formation by inhibiting adipogenesis via KLF15/PPARγ2 signaling in GIO rats

Abstract: Glucocorticoid (GC)-induced osteoporosis (GIO) is characterized by impaired bone formation, which can be alleviated by tanshinol, an aqueous polyphenol isolated from Salvia miltiorrhiza Bunge. In this study we investigated the molecular mechanisms underlying GC-induced modulation of osteogenesis as well as the possibility of using tanshinol to interfere with GIO. Female SD rats aged 4 months were orally administered distilled water (Con), prednisone (GC, 5 mg·kg·d), GC plus tanshinol (Tan, 16 mg·kg·d) or GC pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…Thus, β-catenin is a co-activator of Foxo3a for resistance to oxidative stress. Foxo3a may form a complex with PPARγ to bind to β-catenin, abrogating canonical Wnt/β-catenin signaling 36,37. However, Foxo3a may also bind to the promoter and induce the expression of PUMA, which is a BH3-only pro-apoptoic factor antagonizing Bcl-2 and promoting p53-independent apoptosis in colorectal cancer cells 38.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, β-catenin is a co-activator of Foxo3a for resistance to oxidative stress. Foxo3a may form a complex with PPARγ to bind to β-catenin, abrogating canonical Wnt/β-catenin signaling 36,37. However, Foxo3a may also bind to the promoter and induce the expression of PUMA, which is a BH3-only pro-apoptoic factor antagonizing Bcl-2 and promoting p53-independent apoptosis in colorectal cancer cells 38.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Jiang et al86 demonstrated that pravastatin alleviated steroid-induced osteonecrosis in rats by activating the Wnt signaling pathway and inhibiting PPARγ expression. Studies have shown that tanshinol reduces bone formation damage by inhibiting adipogenesis via PPARγ signaling in glucocorticoid-induced osteoporosis rats 87. This approach may be an attractive strategy to target osteoblastic cells by specific PPARγ inhibitors to treat bone diseases.…”
Section: Resultsmentioning
confidence: 98%
“…Mechanistic exploration showed that Tanshinol upregulated FoxO3a and Gadd45a proteins involved in FoxO3a pathway and suppressed Axin2 and β-catenin involved in canonical Wnt signaling pathway in turn leading to enhancement of osteogenesis. Thus, Tanshinol was shown to counteract impairment of bone formation through KLF15/PPARγ2/FoxO3a/Wnt pathway and abnormal expression of signaling molecules caused by glucocorticoids thus effectively stimulating osteogenesis ( Yang et al, 2018 ). Coadministration of Tanshinol with Calcitriol in GC-induced bone loss model was found to improve bone microarchitecture and inhibit bone loss induced by glucocorticoids through promotion of bone generation and downsurge of bone resorption ( Chen G. et al, 2017 ).…”
Section: Tanshinolmentioning
confidence: 99%